2003
DOI: 10.1021/jp0224160
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes in Phase Transitions of Nylon Model Compounds. 1. Transition Behavior of Model Compounds of R-NHCO-R‘ Type

Abstract: To clarify the essential features of Brill transition of aliphatic nylons, structural changes have been investigated by X-ray diffraction and infrared spectroscopic methods for the compounds CH 3 (CH 2 ) 10 NHCO(CH 2 ) 9 CH 3 (designated as N11) and CH 3 (CH 2 ) 9 NHCO(CH 2 ) 8 CH 3 (N10) which were assumed to be the simplest models of nylons 11/11 and 10/10, respectively. Depending on the preparation conditions, N11 crystallized to the R and γ forms and N10 to the R form at room temperature. Infrared and X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 60 publications
5
50
0
Order By: Relevance
“…The crystalline structure and polymorphism of Nylon 11 has been studied by several researchers [23][24][25][26][27][28]. It has been reported that the α form of Nylon 11 exhibits two characteristic reflections at 2θ = 20.2 and 23.01° [23] whereas the γ form of Nylon 11 exhibits a characteristic reflection at 2θ = 21.34° [24].…”
Section: X-ray Diffractionmentioning
confidence: 99%
“…The crystalline structure and polymorphism of Nylon 11 has been studied by several researchers [23][24][25][26][27][28]. It has been reported that the α form of Nylon 11 exhibits two characteristic reflections at 2θ = 20.2 and 23.01° [23] whereas the γ form of Nylon 11 exhibits a characteristic reflection at 2θ = 21.34° [24].…”
Section: X-ray Diffractionmentioning
confidence: 99%
“…Recent works based on FTIR data suggest that high temperature pseudohexagonal arrangements are a result of the conformational disorder of polymethylene segments rather than of disruption of hydrogen bonds [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…As melting starts around 193 • C, the narrowing and sharpening of the peaks as well as the disappearance of the C1 ␣ and the carbonyl peak at 173.2 ppm are observed. The twisting motion and the weakening of intermolecular hydrogen bonding are accelerated for these carbon sites and become even more pronounced compared to other carbon sites in the repeat unit [23]. Close to the melting temperature of the PA6 (212 • C as the highest temperature applied during the measurements) only the trans and gauche transformers of the rigid amorphous phase are visible.…”
Section: Conformational Changes and Local Chain Packing Analyzed By Smentioning
confidence: 94%
“…The bands at 1477, 1417, 1294, 1237 and 1201 cm −1 can be qualified as Brill bands and the disappearance of these peaks indicate the Brill transition of the copolyamides at around 160-180 • C [20,23]. During this transition, the interchain and intersheet distances of the PA6 chains become equal and the triclinic structure transforms into a pseudohexagonal structure [43].…”
Section: Analysis Of Polymer Chain Conformations By Ft-ir Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation